2019
DOI: 10.3390/su11030706
|View full text |Cite
|
Sign up to set email alerts
|

Developing Active Canopy Sensor-Based Precision Nitrogen Management Strategies for Maize in Northeast China

Abstract: Precision nitrogen (N) management (PNM) strategies are urgently needed for the sustainability of rain-fed maize (Zea mays L.) production in Northeast China. The objective of this study was to develop an active canopy sensor (ACS)-based PNM strategy for rain-fed maize through improving in-season prediction of yield potential (YP 0 ), response index to side-dress N based on harvested yield (RI Harvest ), and side-dress N agronomic efficiency (AE NS ). Field experiments involving six N rate treatments and three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Working with rain-fed maize in North-east China, Wang et al [135] found that rather than GreenSeeker measured NDVI alone, using plant height information together with NDVI improved the prediction of potential yield (with no additional fertilizer N) as well as RI. The improved NFOA (INFOA) based on NDVI combined with relative plant height guided fertilizer N doses for maize better than the NFOA in both black and aeolian sandy soils.…”
Section: Canopy Reflectance Sensor Based Fertilizer Nitrogen Managemementioning
confidence: 99%
“…Working with rain-fed maize in North-east China, Wang et al [135] found that rather than GreenSeeker measured NDVI alone, using plant height information together with NDVI improved the prediction of potential yield (with no additional fertilizer N) as well as RI. The improved NFOA (INFOA) based on NDVI combined with relative plant height guided fertilizer N doses for maize better than the NFOA in both black and aeolian sandy soils.…”
Section: Canopy Reflectance Sensor Based Fertilizer Nitrogen Managemementioning
confidence: 99%
“…However, over-application of N is common in Chinese agriculture, resulting in many environmental problems [2,3]. Precision N management strategies aiming to apply the optimal amount of N fertilizer at the right time and place can help increase crop yield and N use efficiency, as well as reduce N surplus and environmental impacts [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the N topdressing requirement is estimated by dividing the yield gap (YP N − YP 0 ) by the average AE of topdressing N (AE topdressing ) [10]. The AE topdressing should be higher than the one for the whole season, and will be predicted during the growing season using the predicted RI Harvest [30].…”
Section: Development and Evaluation Of Rapidscan-based Precision Nitr...mentioning
confidence: 99%
“…As a result, the PNM strategy making two in-season N recommendations at stem elongation and heading stages only using NDVI had the worst performance among all the PNM strategies evaluated in the scenario analysis. One approach to overcome the NDVI saturation problem is to combine NDVI with relative plant height data [30]. Another approach is to replace NDVI with other VIs that can overcome the saturation effect [32].…”
Section: Selection Of Vegetation Indices For Precision N Management S...mentioning
confidence: 99%